Application of UV–Visible Light Absorption and Scattering technique to low absorption fuels under diesel-like conditions. (1st September 2016) - Pastor, J.V.; García-Oliver, J.M.; López, J.J.; Micó, C.
Abstract: Light Absorption and Scattering technique (LAS) has been applied for the measurement of fuel vapor distribution in diesel-type sprays. This technique is usually limited to fuels with relatively high absorptivity, which are sometimes not commonly used as surrogate fuels. In the present paper, a comparison of fuels with very different absorptive properties has been made to determine the range of application of the methodology. A calibration procedure has been applied to n -decane (DEC), a binary blend of n -decane and n -hexadecane (50DEC) and three blends of n -heptane with a highly-absorpting fuel (HEPB1, HEPB2 and HEPB3). This methodology enables the in-situ quantification of absorption coefficients at high pressure and temperature by creating a uniform mixture inside the cylinder. Results have been later applied for the quantification of fuel vapor distribution in sprays for DEC, 50DEC and HEPB3. Results obtained with these range of fuels have enabled to establish the limit in terms of absorption coefficient needed to get consistent results with the technique.